Naturally occurring hepatitis B virus (HBV) variants with primary resistance to antiviral therapy and S-mutants with potential primary resistance to adefovir in Argentina - Cuestas, María Luján (2010)
Hepatitis B virus (HBV) variants may either emerge in patients with chronic hepatitis B (CHB) as a result of positive selection pressure exerted by their own immune response, or during therapy with nucleos(t)ide analogues (NAs). Naturally occurring HBV variants with primary antiviral resistance are rarely observed. The aim of this study was to retrospectively analyze the (eventual) circulation of HBV variants with natural resistance to NAs currently used as therapy for CHB in Argentina. This study reports 13 cases of CHB-infected patients with natural antiviral resistance to at least one NA. Five of them were also carriers of S-variants that might escape the humoral immune system recognition with potential resistance to adefovir. In addition to the already reported A2 HBV subgenotype association to NAs natural resistance, E and F genotypes association to such resistance is described for the first time. These findings suggest that sequence analysis of the HBV reverse transcriptase might be an essential tool before starting antiviral therapy, in order to choose the proper NAs for optimizing the therapeutic management of chronically infected patients. Moreover, the circulation and transmission of S-mutants with resistance to such antiviral drugs should be of public health concern as they may represent an additional risk for the community.